Is Burnout Primarily Linked to Work-Situated Factors? A Relative Weight Analytic Study - Bianchi, Renzo; Manzano-García, Guadalupe; Rolland, Jean-Pierre (Frontiers in Psychology, 2021)
It has often been asserted that burnout is primarily explained by occupational-context factors, and only secondarily by individual-level (e.g., personality) and nonwork (or general) factors. We evaluated the validity of this view by examining the links between burnout and an array of 22 work-situated (effort-reward imbalance, unreasonable work tasks, unnecessary work tasks, weekly working hours, job autonomy, skill development, performance feedback, and support in work life), work-unrelated (sentimental accomplishment, familial accomplishment, number of child[ren], leisure activities, residential satisfaction, environmental quality, security in daily life, and support in personal life), dispositional (neuroticism, sex, age, and physical condition), and intersecting (work-nonwork conflict and nonwork-work conflict) variables. The study involved schoolteachers from three different countries: France (N = 4,395), Spain (N = 611), and Switzerland (N = 514). Burnout was assessed with the Maslach Burnout Inventory for Educators. Most of our predictors were assessed based on widely used measures (e.g., neuroticism was assessed with the NEO-Five Factor Inventory). In order to assess sentimental accomplishment and familial accomplishment, we created two self-reported measures, namely, the Sentimental Accomplishment Inventory (SAI; 9 items) and the Familial Accomplishment Inventory (FAI; 9 items). The SAI and the FAI both showed strong reliability and high factorial validity. Exploratory structural equation modeling bifactor analysis and Mokken scaling suggested that both instruments could be considered essentially unidimensional. The study results showed that neuroticism, job strain, skill development, security in daily life, and work-nonwork conflict were consistently associated with burnout across the three samples. Sample-specific predictors of burnout included sex, age, unreasonable work tasks, weekly working hours, job autonomy, support in work life, sentimental accomplishment, leisure activities, support in personal life, and nonwork-work conflict. Relative weight analysis indicated that neuroticism was the best predictor of burnout in each sample. Our findings suggest that burnout’s nomological network may not be primarily job-related. We conclude that the tendency to de-emphasize individual-level and nonwork factors in burnout research is unwise. This tendency may constitute a roadblock in the development of effective interventional strategies. The implications of our findings for burnout’s conceptual status are discussed. The neuroticism-burnout link should be further examined in longitudinal studies.